1980
DOI: 10.1029/wr016i003p00517
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Green‐Ampt Model to infiltration under time‐dependent surface water depths

Abstract: The performance of the Green‐Ampt model for infiltration problems where the depth of water above the ground surface is varying with time is investigated. In order to yield infiltration rates that agree with those predicted by the Richards equation for flow in a homogeneous, nondeforming, and nonhysteretic soil the effective suction head parameter in the Green‐Ampt model must be considered a function of time, surface water depth, initial moisture content, and soil type. However, when a constant value of the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 25 publications
2
14
0
2
Order By: Relevance
“…Argyrokastritis et al (2009) showed that after ponding and the transformation of the boundary conditions from flux-controlled to flooding, there is a close coincidence of the moisture profiles for the case of sand mixture, retaining always the Green-Ampt mode of wetting front advancement. Freyberg et al (1980) investigated the performance of the Green-Ampt model for addressing the infiltration problem with time varying water depth. They suggested that the effective suction head must be considered as a function of surface water depth, initial moisture content and soil type.…”
Section: Green-ampt Model For Homogeneous Soilsmentioning
confidence: 99%
“…Argyrokastritis et al (2009) showed that after ponding and the transformation of the boundary conditions from flux-controlled to flooding, there is a close coincidence of the moisture profiles for the case of sand mixture, retaining always the Green-Ampt mode of wetting front advancement. Freyberg et al (1980) investigated the performance of the Green-Ampt model for addressing the infiltration problem with time varying water depth. They suggested that the effective suction head must be considered as a function of surface water depth, initial moisture content and soil type.…”
Section: Green-ampt Model For Homogeneous Soilsmentioning
confidence: 99%
“…If, however, the wetting front reaches the water table, the steady state infiltration component will be influenced by the groundwater flow regime and lateral flow conditions. Equation (2) is valid assuming that sediments are homogeneous to the depth of the wetting front and that water temperature, water quality, discharge, and stage are constant [Freyberg et al, 1980]. For these conditions, equation (2) can be rewritten as…”
Section: Theorymentioning
confidence: 99%
“…However, the Greenand-Ampt infiltration approach turns on an equation without analytical solution for disconnected streams, because in-channel ponding depth and gravitational terms are timedependent (Freyberg et al, 1980). To overcome this difficulty, Freyberg (1983) proposed a numerical solution (trapezoidal quadrature) of the Green-and-Ampt equation for a uniform alluvium.…”
mentioning
confidence: 99%